Policy-makers' views on impact of specialist and advanced practitioner roles in Ireland: the SCAPE study - BEGLEY, CECILY; HIGGINS, AGNES (My University, 2014)
Aim To ascertain and explore the views held by key healthcare policy-makers on the impact of clinical specialist and advanced practice nursing and midwifery roles. Background Specialist and advanced practice roles are common world-wide and were introduced in Ireland in 2000. After experiencing these roles for a decade, the views of healthcare policy-makers were sought as part of a national evaluation. Methods A qualitative, descriptive design was used. Following ethical approval, 12 policy-makers were interviewed in 2010, using a six-part interview schedule. Results Policy-makers believed that specialist and advanced practice roles resulted in better continuity of care, improved patient/client outcomes and a more holistic approach. These clinicians were also said to be leading guideline development, new initiatives in care, education of staff, audit and policy development. They lacked administrative support and research time. Budget cuts and a government- applied recruitment moratorium were said to hamper the development of specialist/advanced practice roles. Conclusion Healthcare policy-makers believe that specialists and advanced practitioners contribute to higher quality patient/client care, particularly at a strategic level. Implications for nursing management These roles could make an important contribution to future health service developments, particularly in relation to chronic-disease management and community care, where more advanced practitioner posts are required
PUBLISHED
Keywords: Midwifery